2001
DOI: 10.1353/mpq.2001.0001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Environmental Measures on Intelligence in Young Children: Growth Curve Modeling of Longitudinal Data

Abstract: Effects of different environmental measures on individual intellectual growth patterns were examined in 105 young children participating in a longitudinal study. Intelligence 4 th edition) was measured at ages 3 through 6 years, and child's environment (HOME and SES) was assessed at age 3 years. Growth curve analyses revealed that HOME scores exerted a constant influence on the expected composite, verbal, and nonverbal intellectual skills at each age. Only SES influenced the rate of growth, specifically non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
28
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 34 publications
5
28
0
2
Order By: Relevance
“…Especially for young children the home environment is very important [16,17], and concrete activities, as, for example, reading aloud are very stimulating [18][19][20]. So far it could be shown that a stimulating environment can affect the development even stronger than the socioeconomic origin [21]. Since disadvantaged children often suffer of worse home environments, a lot of federal programs try to compensate for disadvantages in home environments, for example, Head Start in the United States or Sure Start in the United Kingdom.…”
Section: Influence Of Social Background and Home Environment On Childmentioning
confidence: 99%
“…Especially for young children the home environment is very important [16,17], and concrete activities, as, for example, reading aloud are very stimulating [18][19][20]. So far it could be shown that a stimulating environment can affect the development even stronger than the socioeconomic origin [21]. Since disadvantaged children often suffer of worse home environments, a lot of federal programs try to compensate for disadvantages in home environments, for example, Head Start in the United States or Sure Start in the United Kingdom.…”
Section: Influence Of Social Background and Home Environment On Childmentioning
confidence: 99%
“…And it is precisely young children for whom the home environment is very important (Luster and Dubow 1992) and concrete activities, such as reading aloud, are very stimulating (Denton et al 2001;Schöler et al 2005). So far it could be shown that the effect of a stimulating environment on a child's cognitive development is partially even stronger than the effect of that child's socioeconomic origin (Espy et al 2001). Empirically, immigrants have been found to be less involved, which may lead to a less supportive behaviour and less time spent together (for cultural differences within child-parent-interaction, see Nauck and Özel 1986;Wittmann 1990).…”
Section: The Influence Of Social Background and Involvement In Explaimentioning
confidence: 99%
“…As described by Cherlin et al (1998), the standardization accommodates the need for administration of age-appropriate measures across developmental phases, produces a flat growth curve for the sample as a whole, but permits the study of between-individual differences. Espy et al (2001) suggest that the standard score metric used to describe children's academic performance aids in the interpretability of the study results. They analyzed the effects of different environmental measures on individual intellectual growth patterns and found that the results of the growth curve analyses were similar using standardized and raw scores.…”
Section: Severity Of Prenatalmentioning
confidence: 99%